2021
DOI: 10.3390/ijms222111483
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and Innate Immunity in the Regulation of SARS-CoV-2-Induced Acute Lung Injury: A Review

Abstract: Despite the protracted battle against coronavirus acute respiratory infection (COVID-19) and the rapid evolution of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), no specific and effective drugs have to date been reported. Angiotensin-converting enzyme 2 (ACE2) is a zinc metalloproteinase and a critical modulator of the renin-angiotensin system (RAS). In addition, ACE2 has anti-inflammatory and antifibrosis functions. ACE has become widely known in the past decade as it has been identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 208 publications
(234 reference statements)
0
18
0
Order By: Relevance
“… 2 Initial infection occurs within in the upper airway with increased levels of ACE2 within the neuroepithelium of the nose, 3 explaining the high incidence of anosmia and hyposmia in SARS‐CoV‐2 infections. Studies have implicated ACE2 as major participant in innate immunity 4 and suggested patients on renin‐angiotensin system (RAS) blockers are less likely to have severe disease, 5 , 6 , 7 which re‐enforces how function or prevalence of the receptor may explain disease severity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Initial infection occurs within in the upper airway with increased levels of ACE2 within the neuroepithelium of the nose, 3 explaining the high incidence of anosmia and hyposmia in SARS‐CoV‐2 infections. Studies have implicated ACE2 as major participant in innate immunity 4 and suggested patients on renin‐angiotensin system (RAS) blockers are less likely to have severe disease, 5 , 6 , 7 which re‐enforces how function or prevalence of the receptor may explain disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…The oral and nasal cavities are in close proximity to these tissues and likely associated with increased inflammation as well. Given ACE2's connection to innate immunity and inflammation,4 it may be upregulated in this patient population.Finally, ACE2 RNA expression may have a minor role in actual protein expression and function in infectivity of SARS-CoV-2. Multiple proteins such as TMPRSS2 are involved in SARS-CoV-2 activity and virulence2 and may play an equal or more important role in describing the differences in age virulence.…”
mentioning
confidence: 98%
“…According to the literature, severe SARS-CoV-2 can trigger an excessive immune response, with massive production of inflammatory cytokines and chemical mediators, known as the cytokine storm [ 4 , 5 , 6 , 7 ]. Cytokine levels rise during the systemic inflammatory response syndrome and may lead to multi-organ failure in some individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The virus enters host cells by binding to the angiotensin‐converting enzyme 2 (ACE‐2) receptor in most host cells (Singh et al, 2021 ). Once the SARS‐CoV‐2 spike protein binds to ACE‐2, it downregulates its expression, consequently increasing capillary permeability and causing pulmonary damage (Qu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The virus enters host cells by binding to the angiotensinconverting enzyme 2 (ACE-2) receptor in most host cells (Singh et al, 2021). Once the SARS-CoV-2 spike protein binds to ACE-2, it downregulates its expression, consequently increasing capillary permeability and causing pulmonary damage (Qu et al, 2021). The innate immune system functions as the first line of host defense against pathogens and plays a key role in combating SARS-CoV-2 (Diamond & Kanneganti, 2022).…”
mentioning
confidence: 99%